Draft National Education Policy 2019: An Overview - Kaur, Nimrat (Voices of Teachers and Teacher Educators, 2019)
This paper gives a brief summary of the main issues and recommendations in the chapters on school education and teacher education of the draft NEP 2019. The paper extracts the crucial points that are the most important for the current times.